Frecuencia de lechones de bajo peso al nacimiento y su relación con la sobrevivencia a los ocho días, en seis granjas suinas comerciales de Antioquia, Colombia (1999)
ABSTRACT: From 1802 full-term born piglets in 6 commercial swine farms (n = 160 farrows) of the state-like Antioquia, Colombia, and under the criteria of low birth weight (LBW) under 1000 g, birth weight and 8 days weight was analyzed and associated with: sex, mortality, daily gain, histology and relative weight of liver, thyroids, adrenal glands of born dead and born alive piglets. Data were analyzed by multifactorial Anova and simple regression. There were 1663 born alive (92.14%), 59 mummies (3.27%), and 80 stillbirths (4.59%). Forty percent of stillbirth and 16.18% of born alive piglets were LBW (p < 0.01). The average weight from LBW was 836 (± 14) g and from normal piglets was 1420 (± 7) g (p < 0.01). LBW piglets tented to have higher mortality at birth (p= 0.052), and a significant reduction of their average daily gain and higher mortality at day 8 of age (p < 0.01). LBW piglets did not depend on gender or birth order (p > 0.05); but it was associated with farm, parity, sow body condition and homospermic mating (p < 0.05). Adrenal glands tended to be lighter on underweight piglets than normal piglets (p = 0.09). There were histological differences between normal and LBW piglets for thyroids and adrenal glands. Further studies are required to define the association between LBW piglets and their morphology and weight of adrenal and thyroid glands, and the causes of LBW piglets in the swine industry. Heterospermic matings are used to increase litter size in commercial farms. Our results suggest that heterospermic matings reduce piglet birth weight (p < 0.01).